ANALYSIS OF WORK PRACTICES IN ORGANIZATIONS BASED ON ISLAMIC DOCTRINAL STANDARDS REACHES THE WAY FORWARD - Zanirah Mustafa@Busu; Noraını Junoh; Nurul Hidayah Awang @ Ab Rahman; Nurul Izzah Noor Zainan; Mohd Khairul Anuar Ismail; Nor Asmira Mat Jusoh; Norazmila Yusuf; Nik Muniyati Nik Din; Intan Nurul ‘Ain Mohd Firdaus Kozako (Journal of Islamic, Social, Economics and Development, 2022)
Organizations or government agencies are constantly faced with various forms of threats either from within or outside the environment and these threats can affect the performance, productivity and future of an organization. Today, the average threat to an organization stems from individuals within the organization itself and in turn involves other members who damage the identity of the government organization. Typically, these threats are closely linked to issues of ethics and integrity. Neglect of these two principles can open up opportunities for malpractice, corruption, misconduct and abuse of power in an organization. This article explains the practice of excellent work culture in an organization as stipulated by Islam and applied in the current days. The article exemplifies how Islam stresses on the application of excellent work culture and moral values to be practiced in strengthening an organization. The main purpose of this writing is to identify the elements of work culture in Islam and the characteristics of excellent work culture that every Muslim should know. Apart from that, this writing also aims to describe the challenges in implementing Islamic work culture. In the era of globalization, portraying good work ethics among Muslims is essential. Good work ethics are not only about being a diligent, persistent and loyal workforce, but it is also about being a workforce who integrates Islamic values into their daily life, which do not derail from the values as prescribed in the Qur'an and As-Sunnah. This article also explains how the concepts, conditions, ethics and characteristics of work culture in Islam remain relevant and practicable in today’s society. The basis of work culture for Muslim is to seek the pleasure of Allah SWT. The individual’s connection with God shapes their ethical work culture to be extra careful and diligent in their work practices. They will strive to do their best to obtain the pleasure of God and foster good relationships among their colleagues within the organization. This article also highlights the need for every Muslim to embrace Shariahcompliant practices in all aspects of their work. This writing instrumented the qualitative research as its methodology by conducting a library study of the sources of the Quran and hadith as well as scientific materials such as journal articles, reference books from religious scholars related to the scope of the study topic. The results of this writing can be used as a reference and guidance to increase the level of awareness, open the minds of every Muslim as well as remind each party to fulfill their rights and responsibilities towards every job entrusted to them. Work in the Islamic concept is often associated to the term charity which has a wider scope than simply working for profit or wages. It is hoped that this writing can be used as a guideline or standard for all employees and organizations to work in line with Islamic requirements.